Relational Capabilities under Moderating and Mediating Effects to Understand their Impacts on Firm Financial Performance - PIGOLA, Angelica; COSTA, Priscila Rezende DA; SERRA, Fernando Antonio Ribeiro (International Journal of Business, Economics and Management, 2021)
Relational Capabilities (RC) appear are valuable capabilities not only for performance but also to generate profitability. In this vein, this study performed a meta-analytic investigation of RC dimensions influencing firm financial performance. It also examined the role of mediating and moderating effects of knowledge management and partners integration influencing this association. From a meta-analytic procedure, 54 empirical studies were examined through random-effects model of Pearson’s correlations as the effect size and a meta-analytical regression analysis (MARA) to examined moderation effects and meta-analytical structure equation modeling (MASEM) to examined mediation effects. Our findings confirm that firm financial performance is impacted directly and positively by RC itself excepting by the intrafirm relational capacity dimension. We also find that knowledge management and partner integration do not mediate positively the effect RC on firm financial performance. Further, RC dimensions effects on firm financial performance vary positively and negatively across partner integration and knowledge management moderation effects.